Analysis of psychological and social factors affecting climate change adaptation and mitigation behaviors among Iranian rice farmers - Moslem Savari; Bagher Khaleghi (Scientific Reports)
Abstract Rice is a vital staple crop, feeding billions globally. However, conventional rice farming practices, especially traditional irrigation techniques, are significant contributors to greenhouse gas (GHG) emissions. Flooded irrigation, in particular, creates anaerobic conditions that facilitate methane production—a GHG significantly more potent in terms of global warming potential compared to carbon dioxide. As a result, rice cultivation is a key driver of climate change (CC). Addressing these environmental challenges while maintaining sustainable productivity requires the adoption of climate-smart agricultural practices. This study explores the factors influencing the adaptation and mitigation behaviors of Iranian rice farmers in response to CC. Utilizing the Theory of Planned Behavior (TPB) and Value-Belief-Norm (VBN) theory as theoretical frameworks, the research examines psychological and normative drivers that shape farmers’ decision-making. This research was carried out in Shushtar County, located in Iran’s Khuzestan Province in the southwest. The study utilized a structured survey tool, and the collected responses were analyzed through structural equation modeling (SEM). The results indicate that TPB more effectively explains adaptation intentions, while VBN provides greater insight into mitigation behaviors. The integrated TPB-VBN model accounts for 64.2% of the variance in adaptation intentions and 67.6% in mitigation intentions. These findings offer valuable insights for policymakers aiming to foster sustainable rice farming practices that align with CC adaptation and mitigation objectives.